EFEKTIVITAS MODEL PEMBELAJARAN HYBRID DALAM KETERAMPILAN MENULIS CERPEN SISWA KELAS XI SMAIT AL USWAH BANGIL - Saefuddin Famsah (BASA Journal of Language & Literature, 2022)
Some students find writing short stories difficult and boring. One way to improve writing skills is to use a hybrid learning model. It is a type of learning that combines various methods to help learn new information. Hybrid learning is a learning model that combines traditional face-to-face and online learning resources. This allows for smarter learning experiences for both students and teachers. The purpose of this study was to test the effectiveness of the hybrid learning model in the short story writing skills of class XI SMAIT Al Uswah Bangil. This type of research uses a pre-experimental design with one group pretest-posttest. Collecting data in this study using a questionnaire. The results of data analysis using the different test, namely the Paired sample t-test, found that the p value was 0.000 <α 0.05, which means that the results of the study showed that the hybrid learning model proved effective in short story writing skills for class XI students at SMAIT Al Uswah Bangil.